An Anti-EGFR IgA That Displays Improved Pharmacokinetics and Myeloid Effector Cell Engagement In Vivo - Lohse, Stefan; Meyer, Saskia; Meulenbroek, Laura A P M; Jansen, J H Marco; Nederend, Maaike; Kretschmer, Anna; Klausz, Katja; Möginger, Uwe; Derer, Stefanie; Rösner, Thies; Kellner, Christian; Schewe, Denis; et al. (American Association for Cancer Research Inc., 2016)
Antibodies of IgA isotype effectively engage myeloid effector cells for cancer immunotherapy. Here, we describe preclinical studies with an Fc engineered IgA2m(1) antibody containing the variable regions of the EGFR antibody cetuximab. Compared with wild-type IgA2m(1), the engineered molecule lacked two N-glycosylation sites (N166 and N337), two free cysteines (C311 and C472), and contained a stabilized heavy and light chain linkage (P221R mutation). This novel molecule displayed improved production rates and biochemical properties compared with wild-type IgA. In vitro, Fab- and Fc-mediated effector functions, such as inhibition of ligand binding, receptor modulation, and engagement of myeloid effector cells for antibody-dependent cell-mediated cytotoxicity, were similar between wild-type and engineered IgA2. The engineered antibody displayed lower levels of terminal galactosylation leading to reduced asialoglycoprotein-receptor binding and to improved pharmacokinetic properties. In a long-term in vivo model against EGFR-positive cancer cells, improved serum half-life translated into higher efficacy of the engineered molecule, which required myeloid cells expressing human FcαRI for its full efficacy. However, Fab-mediated effector functions contributed to the in vivo efficacy because the novel IgA antibody demonstrated therapeutic activity also in non-FcαRI transgenic mice. Together, these results demonstrate that engineering of an IgA antibody can significantly improve its pharmacokinetics and its therapeutic efficacy to inhibit tumor growth in vivo.
Keywords: Animals; Antibodies, Anti-Idiotypic; Cell Differentiation; Humans; Immunotherapy; Mice; Mice, Inbred BALB C; Mice, SCID; Mice, Transgenic; Myeloid Cells; Receptor, Epidermal Growth Factor; Transfection; Taverne; Journal Article; Research Support, Non-U.S. Gov't